O boi bumbá de Parintins: a evolução da toada numa perspectiva dos ecossistemas de comunicação - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
In this dissertation I present the evolution of the culture music of Boi Bumbá from Parintins - municipality of Amazonas state - as a mass/popular culture where it shows its symbolic power by referencing a legacy left by the ancestors forming a unique identity in the city's population. The cultural hybridizations suffered/imposed over time caused a significant change regarding the shape of the whole folklore ensemble, especially in the genre music of the Parintinense folk festival, causing an evolution in the format of the lyrics, melody, musicality and arrangement. The old folk songs was simple poetry that marked the daily life of Amazonian composers and their actors. From the early nineties to the present day the folks songs and all its attributes is musically complex and quite different from what it was. This musical transformation/evolution adapts to the demands of the entertainment market imposed by the cultural industry. From a communicational ecosystem look, it is observed that communication, now in digital format, plays a major role in the publication and propagation of transformed folk songs, based on internet-based networking technologies.
Keywords: Cultura popular - Parintins (AM); CIENCIAS SOCIAIS APLICADAS; Ecossistema de Comuniação; Toada de Parintins; Boi bumbá; Folclore; Evolução musical